Socio-legal significance of family waqf in Islamic Law: Its degradation and revival - Sadique, Muhammad Abdurrahman; Ansari, Abdul Haseeb; Hingun, Mohsin; Hasan, Aznan (IIUM Press, 2016)
From a Shari’ah perspective, no essential difference is noticed between public welfare waqf and a waqf created for the benefit of individuals such as descendants and family of a person, and both are treated as recommended avenues for voluntary gratuitous transfer of benefits. Over the centuries, family awqaf have degenerated due to various social and political factors. Under the influence of the English law that regards family trusts as non-charitable, family awqaf have been treated as non-charitable institutions, and have been deprived of the privileges and immunities granted to charitable awqaf. In this context, the current article discusses the essential nature of such awqaf with regard to their position in Islamic law and history as well as their social significance, and attempts to shed light on the degeneration that took place in the recent past, while exploring means of revival. It finds that the creation of endowments for specific beneficiaries such as waqf for those related to the endower is a recognised form of charity in Islamic law, that function as public serving entities directly or indirectly. Issues encountered in such awqaf do not necessitate denying their multiple advantages. Providing the necessary legal regulation and administrative framework as well as tax exemption for all awqaf could go a long way in promoting the cause of waqf.